Single-issue Ratifiers or Political Deliberators? - Stefanie Pukallus (International Review of Public Policy)
This paper examines how the European Commission interprets and applies the participatory norm in practice according to constructed strategic contexts. By taking a historical comparative approach and focusing on two examples it shows how, following the Maastricht ‘crisis’ (1992-1998), the participatory norm in the form of debate and dialogue referred simply to a restricted discussion of Single Market rights (DD1). This was a rather limited, one-phased technical discussion on a single issue with an attendant conception of the public as single-issue ratifiers of already existing policies. In contrast, the aftermath of the Constitutional ‘crisis’ (2005-09) led to a conception of debate and dialogue as ‘open-ended’ (DD2); that is, a reflexive wide-ranging amorphous discussion on various and almost randomly chosen topics. DD2 assumed a public of able political discussants, of reflexive and skilful deliberators. What DD1, DD2 and their respective publics show is that when the participatory norm is applied, neither the form of debate and dialogue nor the publics are necessarily defined through universal democratic principles of political involvement and entitlements but rather in terms of expediency and contingent abilities to meet the needs of the European Commission’s strategic agenda at any one time.